PERANAN ABU SEKAM PADI UNTUK MENGURANGI POROSITAS CONBLOCK RINGAN SEKAM PADI - . Bakri (Forestry Faculty of Universitas Hasanuddin, 2012)
This research aimed to determine the role of rice husk ash as pozzolanic material in reducing porosity of lightweight rice husk-conblock. Rice husk ash was obtained by burning rice husk conventionally in kiln drum and subsequently followed by burning in furnace of 1400 Barnsted Thermolyne Type at temperature 600 oC for 2 hours. Sample test preparation and procedure of porosity was adopted from ASTM C 140. Rice husk ash significantly reduced the porosity at all treatment combinations of rice husk ash percentage, but the lower porosity (31 %) obtained by using rice husk ash of 20 %. Key words: rick husk, rice husk ash, lightweight conblock, porosity